Designing a three levels poster to visualize chemical reactions. (3rd April 2021) - Shehab, Saadeddine
Abstract: Activities that engage high school students in visualizing chemical phenomena can help them develop representational competence to think about and communicate their understanding of these phenomena. This paper presents a collaborative learning activity that can engage precollege students in designing a poster that describes four different types of chemical reactions at the Macro, Micro, and Symbolic levels of representation. In this activity, students will work in groups to create the poster and identify the connections between the different levels of representations in order to understand and explain the mechanisms underlying the different types of chemical reactions. The activity can be performed in in-person or virtual classrooms.